Selecting Benchmarking Partners Using Analytical Hierarchy Process Approach - Sari Wulandari; Muhammad Arfidh; Ardian Cahya Utama (School of Industrial and System Engineering, Telkom University, 2020)
Benchmarking is a method to improve performance and improve company competitiveness. This method has been commonly practiced by large companies and has recently been extended to small and medium enterprises (SMEs). However, the implementation between large and SMEs is very different. These differences are debated as an impact of company characteristics, specifically differences in the ability to develop and improve business. Typical SMEs face tough challenges to overcome their resource constraints. This limitation affects the decisions of SMEs in choosing their comparison partners. This research was conducted to fill the research gap regarding the use of the Benchmarking method and the AHP approach to SMEs, especially in determining Benchmark partners using the AHP approach. The use of benchmarking and AHP is illustrated by using SME objects that are engaged in the fashion sector, namely UKM Cotton.Go. The problem faced by UKM Cotton.Go is marketing communication that is not effective in creating sales so it needs to be determined benchmarking partner in making improvements to marketing communication. The use of AHP in determining benchmark partners helps SMEs to find out which benchmark partners have the best marketing communication performance.